HOTTIP-miR-205-ZEB2 Axis Confers Cisplatin Resistance to Ovarian Cancer Cells - Dong, Yu-Jie; Feng, Wei; Li, Yan (Frontiers in Cell and Developmental Biology, 2021)
Ovarian cancer is a deadly gynecological malignancy with resistance to cisplatin a major clinical problem. We evaluated a role of long non-coding (lnc) RNA HOTTIP (HOXA transcript at the distal tip) in the cisplatin resistance of ovarian cancer cells, using paired cisplatin sensitive and resistant A2780 cells along with the SK-OV-3 cells. HOTTIP was significantly elevated in cisplatin resistant cells and its silencing reversed the cisplatin resistance of resistant cells. HOTTIP was found to sponge miR-205 and therefore HOTTIP silenced cells had higher levels of miR-205. Downregulation of miR-205 could attenuate HOTTIP-silencing effects whereas miR-205 upregulation in resistant cells was found to re-sensitize cells to cisplatin. HOTTIP silencing also led to reduced NF-κB activation, clonogenic potential and the reduced expression of stem cell markers SOX2, OCT4, and NANOG, an effect that could be attenuated by miR-205. Finally, ZEB2 was identified as the gene target of miR-205, thus completing the elucidation of HOTTIP-miR-205-ZEB2 as the novel axis which is functionally involved in the determination of cisplatin resistance in ovarian cancer cells.